Effect of α-tocopheryloxy acetic acid, a vitamin E derivative mitocan, on the experimental infection of mice with Plasmodium yoelii - Kasumi Kawamura; Aiko Kume; Rika Umemiya-Shirafuji; Shunji Kasai; Hiroshi Suzuki (Malaria Journal, 2021)
Abstract Background Malaria parasites are known to be vulnerable to oxidative stress. In this study, the effects of the administration of α-tocopheryloxy acetic acid (α-TEA), which is a vitamin E analogue mitocan, on Plasmodium yoelii infection in mice were examined. Methods Alpha-TEA was mixed with diet and fed to C57BL/6J mice before and/or after infection. For parasite infection, 4 × 104 red blood cells infected with P. yoelii (strain 17XL) were inoculated by intraperitoneal injection. In another series of experiment, the effect of the oral administration of α-TEA on P. yoelii 17XL infection in mice was examined. Finally, the combined effect of α-TEA and dihydroartemisinin or chloroquine on P. yoelii 17XL infection was examined. Results When 0.25% α-TEA was mixed with the diet for 7 days before infection and 14 days after infection (in total for 21 days), for 14 days after infection, and for 11 days from the third day after infection, all P. yoelii 17XL-infected mice survived during the observation period. However, all control mice died within 12 days after infection. These results indicated that α-TEA functions effectively even when administered post-infection. The oral administration of α-TEA for P. yoelii 17XL infection was also significant. Although the infected mice in the solvent control died within 10 days after infection, 90% of the mice infected with P. yoelii 17XL survived during the observation period when treated with 10 mg/head/day of α-TEA for 3 days from day 3 after infection. Although the combined effect of α-TEA and dihydroartemisinin (DHA) or chloroquine on P. yoelii 17XL infection was significant, no synergistic or additive effects were observed from the survival curve. Conclusions This study showed the beneficial effects of α-TEA on the experimental infection of mice with P. yoelii 17XL. The stimulatory action of α-TEA on mitochondria and the accompanying reactions, such as reactive oxygen species production, and induction of apoptosis might have some effect on malarial infection.